Protecting Inuit Language and Culture from Linguistic and Cultural Imperialism: Resisting English Dominance through Inuit Qaujimajatuqangit, Community-Driven Educational Reform and Social Media in Nunavik - MacDonald, Natasha (Études Inuit Studies, 2025)
This Inuit-led research explores Inuit voices on decolonizing English second-language (ESL) education in Nunavik by examining how Inuit adults and youth envision protecting Inuktitut and culture while framed by Inuit Qaujimajatuqangit. Thirty-two Inuit adults and 11 youth from three Nunavik communities participated in this research from January to September 2024. They called for decolonizing education by returning to traditional values (IQ) and for schools to uphold Inuit identity and language. The youth identified social media as a key tool for language and cultural preservation, while the adults emphasized the importance of critical dialogue on culture and language within the community. This study contributes to the decolonial discourse in Inuit education by offering an original Inuit-specific methodological framework, Silattusarniq, for research that centers Inuit voices and perspectives on decolonization.